The antibacterial activity of clove oil/chitosan nanoparticles embedded gelatin nanofibers against Escherichia coli O157:H7 biofilms on cucumber - Cui, Haiying; Bai, Mei; Rashed, Marwan M.A.; Lin, Lin (International journal of food microbiology, 2018)
This study aims to evaluate the antibacterial activity of clove oil-loaded chitosan nanoparticles (CO@CNPs) and gelatin electrospun nanofibers against Escherichia coli O157:H7 (E. coli O157:H7) biofilms on cucumbers. The optimal CO@CNPs were prepared when the initial concentration of clove oil (CO) was 2.5mg/mL according to the ionic crosslinking method. CO@CNPs showed high antibacterial activity against E. coli O157:H7 biofilms. After 8h treatment, almost 99.98% reduction in E. coli O157:H7 population was achieved when CO@CNPs were applied at 30% (w/v). Subsequently, the prepared CO@CNPs were incorporated successfully within gelatin nanofibers by electrospinning. After 9mg/mL gelatin/CO@CNPs treatment for 24h, the population of E. coli O157:H7 biofilm reduced by about 99.99% in vitro. Further, the application of gelatin/CO@CNPs nanofibers on cucumber against E. coli O157:H7 biofilm was evaluated as well. After 6mg/mL and 9mg/mL gelatin/CO@CNPs nanofibers treatment at 12°C for 4days, 4.28 and 4.97 log10 reductions of E. coli O157:H7 biofilm in population were observed, respectively. Finally, the sensory evaluation results implied that the gelatin/CO@CNPs nanofibers treatment could maintain the color and flavor of cucumber well for >4days. •The clove oil-loaded chitosan nanoparticles (CO@CNPs) were prepared.•The gelatin nanofibers containing CO@CNPs was prepared by electrospinning.•The gelatin nanofibers can eliminate E. coli O157:H7 biofilms.•The gelatin nanofibers can maintain sensory quality of cucumber.